A Cross-cultural Mixed Methods Investigation of Language Socialization Practices. (28th December 2018) - Ganek, Hillary; Nixon, Stephanie; Smyth, Ron; Eriks-Brophy, Alice
Abstract: This embedded mixed methods study explores how cultural differences in language socialization practices influence parent–child verbal interactions. The Language ENvironment Analysis (LENA) System audio recorded families of children who are and are not deaf and hard of hearing in Canada and Vietnam. Software automatically calculated an average conversational turn count. Canadian families participated in more turns than Vietnamese families regardless of hearing status. Interviews with the children's caregivers provided context for these results. Within Vietnamese families, the language socialization practice "Intelligence" results in reduced opportunities for turn-taking, while the Canadian focus on creating personal "Identity" encouraged them. "Intelligence" encompasses Vietnamese participants' desire to ensure their children are learning and "Identity" expresses the Canadian participants' appeal to encourage individuality in their children. The findings suggest directions for the adaptation of intervention. It is the first known study to incorporate LENA results into a mixed methods design.